Diagnosis of anaplastic lymphoma kinase‐negative anaplastic large cell lymphoma on pleural fluid cytology. Issue 12 (18th August 2021) - Greenland, Nancy Y.; Lu, Chuanyi M.; Cook, Stephen; Peng, Yue
Abstract: ALK‐negative anaplastic large cell lymphoma (ALCL) is an aggressive non‐Hodgkin T‐cell lymphoma. Compared to ALK‐positive ALCL, patients with ALK‐negative ALCL typically are older, present with nodal disease, and have lower survival rates. We report a unique presentation of ALK‐negative ALCL in a pleural fluid. Cell block preparation enabled both confirmation of the diagnosis via immunohistochemical staining and gene rearrangement testing for prognostic information.